Primary care providers' comfort in caring for cancer survivors: Implications for risk‐stratified care. Issue 4 (30th December 2022) - Nekhlyudov, Larissa; Snow, Craig; Knelson, Lauren P.; Dibble, Kate E.; Alfano, Catherine M.; Partridge, Ann H.
Abstract: Personalized, risk‐stratified care aims to "right size" the involvement of primary care providers (PCPs), oncology and specialized practitioners in caring for cancer survivors. Our survey found limited comfort among PCPs in cancer surveillance and management of treatment‐related effects. In hypothetical case scenarios, PCPs reported least comfort in caring for a survivor of childhood cancer, followed by young adult‐onset cancer, and greater comfort in caring for a survivor of adult‐onset breast cancer. While education and training of PCPs is essential, risk‐stratification strategies need to identify patients who may transition to primary care and those who may require ongoing survivorship‐focused follow‐up.